IoT 보안 응용을 위한 경량 블록암호 LEA-128/192/256의 효율적인 하드웨어 구현 - 성미지(Mi-Ji Sung); 신경욱(Kyung-Wook Shin) (한국정보통신학회논문지, 2015)
This paper describes an efficient hardware implementation of lightweight encryption algorithm LEA-128/192/256 which supports for three master key lengths of 128/192/256-bit. To achieve area-efficient and low-power implementation of LEA crypto- processor, the key scheduler block is optimized to share hardware resources for encryption/decryption key scheduling of three master key lengths. In addition, a parallel register structure and novel operating scheme for key scheduler is devised to reduce clock cycles required for key scheduling, which results in an increase of encryption/decryption speed by 20~30%. The designed LEA crypto-processor has been verified by FPGA implementation. The estimated performances according to master key lengths of 128/192/256-bit are 181/162/109 Mbps, respectively, at 113 MHz clock frequency. 128/192/256-비트의 마스터키 길이를 지원하는 경량 블록암호 알고리듬 LEA-128/192/256의 효율적인 하드웨어 설계를 기술한다. 저면적, 저전력 LEA 프로세서 구현을 위해 세 가지 마스터키 길이에 대한 암호/복호 키 스케줄링의 하드웨어 자원이 공유되도록 설계를 최적화하였다. 또한, 키 스케줄러의 병렬 레지스터 구조와 새로운 동작방식을 고안하여 키 스케줄링에 소요되는 클록 수를 감소시켰으며, 이를 통해 암호/복호 동작속도를 20~30% 향상시켰다. 설계된 LEA 프로세서는 FPGA 구현을 통해 하드웨어 동작을 검증하였으며, 113 MHz 클록으로 동작하여 마스터키 길이 128/192/256-비트 모드에서 각각 181/162/109 Mbps의 성능을 갖는 것으로 평가 되었다.